2018
DOI: 10.3389/fpsyg.2018.01499
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Validity and Measurement Invariance of the Slovene Version of the Cultural Intelligence Scale

Abstract: This study examined the factorial validity of the Slovene version of the cultural intelligence scale (CQS) in a representative sample of 1,000 Slovenian participants (49% were female). The results of confirmatory factor analysis supported the factorial validity of the Slovene CQS and the existence of a general (second-order) cultural intelligence factor. The four scales and the overall (general) CQS scale showed satisfactory internal consistency. The results of multiple-group confirmatory factor analyses suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Furthermore, anxiety control and emotional intelligence are necessary not only on the day of competition but also in the preparation period, when athletes have to manage their weight and deal with a stressful training program (Merino Fernández et al, 2020 ). Previous studies have to some extent identified the variables that can be considered as KPIs for judo performance; these including weight management (Escobar-Molina et al, 2016 ; Thomson et al, 2017 ; Gallot et al, 2019 ), level of strength (Ache Dias et al, 2012 ; Franchini et al, 2019 ), technical and tactical skills (Weigelt et al, 2011 ; Bocioaca, 2014 ; Miarka et al, 2020 ), level and direction of motivation (Gillet et al, 2010 ; Boughattas et al, 2017 ; Oliveira et al, 2018 ), nutrition (Artioli et al, 2019 ), capacity for focus and attention (Yahija, 2010 ; Jacini et al, 2012 ; Mihailescu and Sava, 2013 ; Toh et al, 2018 ; Campos Faro et al, 2020 ), sleep habits (Chtourou et al, 2018 ; Knowles et al, 2018 ; Vlahoyiannis et al, in press ), speed (Almansba et al, 2008 ), and level of conditioning capacity (aerobic and anaerobic; Detanico et al, 2012 ; Franchini et al, 2014 , 2016 ; Hesari et al, 2014 ; Anthierens et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, anxiety control and emotional intelligence are necessary not only on the day of competition but also in the preparation period, when athletes have to manage their weight and deal with a stressful training program (Merino Fernández et al, 2020 ). Previous studies have to some extent identified the variables that can be considered as KPIs for judo performance; these including weight management (Escobar-Molina et al, 2016 ; Thomson et al, 2017 ; Gallot et al, 2019 ), level of strength (Ache Dias et al, 2012 ; Franchini et al, 2019 ), technical and tactical skills (Weigelt et al, 2011 ; Bocioaca, 2014 ; Miarka et al, 2020 ), level and direction of motivation (Gillet et al, 2010 ; Boughattas et al, 2017 ; Oliveira et al, 2018 ), nutrition (Artioli et al, 2019 ), capacity for focus and attention (Yahija, 2010 ; Jacini et al, 2012 ; Mihailescu and Sava, 2013 ; Toh et al, 2018 ; Campos Faro et al, 2020 ), sleep habits (Chtourou et al, 2018 ; Knowles et al, 2018 ; Vlahoyiannis et al, in press ), speed (Almansba et al, 2008 ), and level of conditioning capacity (aerobic and anaerobic; Detanico et al, 2012 ; Franchini et al, 2014 , 2016 ; Hesari et al, 2014 ; Anthierens et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to find within the scientific literature studies that have dealt with linking judo KPIs with performance. Some authors have investigated the impact of weight loss on performance (Artioli et al, 2010 ; Fortes et al, 2017 ), while others have analyzed how the time of day influences explosive performance and psychological variables in elite judokas (Chtourou et al, 2018 ). The relationship between technical-tactical behaviors (Miarka et al, 2017 ) and physical capacities (Kons et al, 2018 ) has also been a focus of attention.…”
Section: Introductionmentioning
confidence: 99%
“…, Khodadady & Ghahari, (2011), Bücker et al, (2016, Boštjančič et al (2018), Gozzoli & Gazzaroli (2018)…”
mentioning
confidence: 99%